Buscando a ciber-harmonia: diálogo entre a consciência corporal e os meios eletrônicos - Cordeiro, Analivia (2004)
This thesis has four complementary items: the sites http://www.totalbody.com.br and http://www.notaanna.com.br, the DVD Total Body and the written theory. To assimilate its content, you have to read the texts and exercise your body. To out this research into perspective, I observe today millions of people who are affected by daily use of electronic devices. This routine infiltrates the human relationships, arousing the need for reflection about its influence in people s behavior. These instruments dictate physical and emotional behaviors which mold the body, transforming into daily habits which can cause suffering and pain, such as tendinites. In other words: if we consider the body as a bone structure, covered with skin and full of diversified tissues, we can say the daily use of this body can change its structural and functional features. So, although these tissues are naturally made to resist mechanical efforts like bending, twisting, tearing and pressing; their structure and behavoir can change cronically , if they are excessivelly taxed by repetitive efforts. Within this point of view, this study intends to contribute to personal equilibrium in the sphere of body movements. Nowadays there are many suggestions for equilibrium; from medical treatments to religious rituals but there are no proposals for an organically balanced use of the new electronic equipments. The Total Body DVD is a proposal in this direction. It associates corporal practice with the electronical language in a way the body can creatively experience a wholosome life involving the physical, mental, sensitive and emotional aspects. In order to do this, we use the following theoretical tools: the Endobiophilia, the Eutonia, the Feldenkrais Method and the Laban Method, in the corporal counsciousness field; and Nota-Anna, a software to read, write and learn body movements, in the field of technology.